Komunikasi Bisnis Pelaku Usaha Mebel (Studi Deskriptif Kualitatif Komunikasi Bisnis Pelaku Usaha Mebel Di Dukuh Mutihan-Mojosawit, Desa Serenan, Kecamatan Juwiring, Kabupaten Klaten Dalam Menjaga Keberadaan Bisnis Mebel) - PRASETYO, SOFVAN (2016)
Running a business is not an easy thing. Employers should make relationships with all parties associated with the business. Communication needed to make a relationship. With good communication, the relationship that is created can be used to solve all the problems that exist in running business. By using all forms of communication including verbal and nonverbal communication, communication can be directed to achieve specific goals. The purpose of this study was to determine the business communication conducted by furniture producers in Mutihan-Mojosawit Orchard, Serenan Village, Juwiring Subdistrict, Klaten Regency in establishing and maintaining communication with stakeholders in maintaining the presence of the furniture business. The informant in this research are three people that have been running business above 10 years and have worker bellow 5 people. In assessing this, required an effort to be able to uncover the truth behind the communications that take place between employers and stakeholders. In this study using quantitative descriptive method to disclose it. In-depth interviews needed to dig deeper information to reveal facts. The results of this research indicate communication made by employers simply unchecking necessarily only establish communication, but also to maintain communication in order not to break up, so it can continue the business relationship that will impact on the profit obtained by furniture businesses. Communication is established with both able to overcome all the problems exist in furniture business such as capital and so forth. All forms of conflict can be complete by providing good communication. The most fundamental among them all is the communications business that make the relationship amongst employers.